Advances on Emerging Materials for Flexible Supercapacitors: Current Trends and Beyond. (9th August 2020) - Benzigar, Mercy R.; Dasireddy, Venkata D. B. C.; Guan, Xinwei; Wu, Tom; Liu, Guozhen
Abstract: The progressive size reduction of electronic components is experiencing bottlenecks in shrinking charge storage devices like batteries and supercapacitors, limiting their development into wearable and flexible zero‐pollution technologies. The inherent long cycle life, rapid charge–discharge patterns, and power density of supercapacitors rank them superior over other energy storage devices. In the modern market of zero‐pollution energy devices, currently the lightweight formula and shape adaptability are trending to meet the current requirement of wearables. Carbon nanomaterials have the potential to meet this demand, as they are the core of active electrode materials for supercapacitors and texturally tailored to demonstrate flexible and stretchable properties. With this perspective, the latest progress in novel materials from conventional carbons to recently developed and emerging nanomaterials toward lightweight stretchable active compounds for flexi‐wearable supercapacitors is presented. In addition, the limitations and challenges in realizing wearable energy storage systems and integrating the future of nanomaterials for efficient wearable technology are provided. Moreover, future perspectives on economically viable materials for wearables are also discussed, which could motivate researchers to pursue fabrication of cheap and efficient flexible nanomaterials for energy storage and pave the way for enabling a wide‐range of material‐based applications. Abstract : Modern supercapacitors with high energy storage and light weight formula are a competitive market in this era. Significant developments in their designs and ease of use are moving towards flexible and wearable patterns. But the core of such devices rely on material innovations and performance. Here, the underlining challenges, current trends, and future scope are presented accordingly.